Konsep Masjid Sebagai Pusat Pendidikan Islam - Muhammad Tasmin (Rayah Al-Islam, 2020)
Mosque with a rapid development in Indonesia should become a pride as a Moslems asset. Unfortuntely, the development of mosque, physically, has not synergize with the management of the mosque, such as the presence of the prophet mosque in in Madinah wich was having function as the central of people’s Education. Writer felt summoned to particulize a mosque that had started to organize it’s management, Ar Riyadh mosque in Gunung Tembak, Balikpapan, to ascertain how far that mosque can become a refference of mosque concept as a central of Islamic Education. According to the data and writer’s description, it is discovered that Ar Riyadh Mosque having an educational program for whole people of the mosque with 4 kinds of services; first, covering the general activities wich are including khutbah in Friday and general recitation, second, Taklim Diniyah after maghrib, third, Halaqah Diniyah after subuh, forth, a specific education for ulama and zu’ama. With this intensive education, writer concluded that Ar Riyadh Mosque is able to become a mosque concept as a central of Islamic Education, with the improvement of planning aspects, evaluation, self-funding engineering and muslimat services.